THE UNITED STATES INTEREST BEHIND THE NORTH KOREA MISSILE CRISIS - Sugeng Riyanto (UIR Press, 2019)
Conflict in the Korean Peninsula has been started since the Korean war 1950-1953, and still, there is no peaceful achievement to end it. Several efforts have been held to solve peacefully, such as bringing North Korea to be a part of the Non-Proliferation Treaty (NPT). U.S. former president, Jimmy Carter, also initiated Agreed Framework, a scheme of resolution of nuclear energy by involving the United States, South Korea, and Japan. Since 2003, Russia, China joint to the United States, South Korea, Japan, and North Korea to start the negotiation over nuclear issues in North Korea, but after the fifth round of these series, no significant achievement attained. Since there is still a threat to Japan and South Korea, the U.S. presence in East Asia gets raison detre’. Besides, there are chances to U.S. in this conflictual situation to promote its weaponry system. Based on its experience in the Gulf War, the United States can also introduce and sell weaponry system, especially the missile technology. This paper tries to explore the advantage of the U.S. in the conflictual situation.